2000
DOI: 10.1038/sj.onc.1203253
|View full text |Cite
|
Sign up to set email alerts
|

PSM, a mediator of PDGF-BB-, IGF-I-, and insulin-stimulated mitogenesis

Abstract: PSM/SH2-B has been described as a cellular partner of the FceRI receptor, insulin receptor (IR), insulin-like growth factor-I (IGF-I) receptor (IGF-IR), and nerve growth factor receptor (TrkA). A function has been proposed in neuronal dierentiation and development but its role in other signaling pathways is still unclear. To further elucidate the physiologic role of PSM we have identi®ed additional mitogenic receptor tyrosine kinases as putative PSM partners including platelet-derived growth factor (PDGF) rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 47 publications
7
57
1
Order By: Relevance
“…Although close association between SH2B1 expression and NSCLC metastasis has been established in our study, the possible mechanisms are still unclear that needed further investigations. Recent some studies have suggested that SH2B1 participate in tumor metastasis through its regulation of processes intrinsic to tumor cells and the surrounding tumor microenvironment depending on the interaction with multiple ligand-activated receptor tyrosine kinases, PDGF , IGF-I , FGFR3 , leptin and so on (Tsuchiya et al, 1999;Riedel et al, 2000;Yousaf et al, 2001;Kong et al, 2002;Somasundar et al, 2004), which may be a good illumination to tumor metastasis. In addition, the results of 108 archival NSCLC patients investigated by immunohistochemistry revealed that high SH2B1 expression level was closely associated with tumor grade, tumor size, clinical stage, lymph node metastasis and recurrence, which indicated the importance of SH2B1 in NSCLC progression and metastasis after surgical resection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although close association between SH2B1 expression and NSCLC metastasis has been established in our study, the possible mechanisms are still unclear that needed further investigations. Recent some studies have suggested that SH2B1 participate in tumor metastasis through its regulation of processes intrinsic to tumor cells and the surrounding tumor microenvironment depending on the interaction with multiple ligand-activated receptor tyrosine kinases, PDGF , IGF-I , FGFR3 , leptin and so on (Tsuchiya et al, 1999;Riedel et al, 2000;Yousaf et al, 2001;Kong et al, 2002;Somasundar et al, 2004), which may be a good illumination to tumor metastasis. In addition, the results of 108 archival NSCLC patients investigated by immunohistochemistry revealed that high SH2B1 expression level was closely associated with tumor grade, tumor size, clinical stage, lymph node metastasis and recurrence, which indicated the importance of SH2B1 in NSCLC progression and metastasis after surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…SH2B1 interacts with the activation loop of TrkA and plays a specific role in TrkA-mediated differentiation in human neuroblastoma cells , as well as axonal survival in primary sympathetic neurons (Eggert et al, 2000). In addition, microinjection of the SH2 domain into transformed fibroblasts partially restored a normal actin stress fiber pattern suggesting a stimulatory role of SH2B1 in normal and malignant cell proliferation (Riedel et al, 2000). These studies suggested that SH2B1 plays a fundamental role in receptor tyrosine kinase-mediated cellular functions and physiologic and pathologic activities of many cancers.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…All four SH2B1 isoforms are able to increase the mitogenic response to epidermal growth factor, IGF-1, and PDGF-BB [14,69] . SH2B1 increases the ability of RET to promote transformation of NIH 3T3 cells [64] .…”
Section: Sh2b1 Promotes Mitogenesis and Transformationmentioning
confidence: 99%
“…The use of cell penetrating peptides, like the HIV peptide TAT, has the advantage of avoiding this pathway and taking the cargo directly into the cell. TAT-mediated cytoplasmic uptake of drug conjugated polymers [9,10], plasmid DNA [10], bacteriophages [11], magnetic nanoparticles of about 10-20 nm in diameter [12] and even liposomes having a diameter of 200 nm [13] has been documented in the literature [14][15][16][17]. Until now the mechanism of internalization of TAT peptide is unclear.…”
Section: Introductionmentioning
confidence: 99%